Excess psychosocial burden in women with diabetes and premature acute coronary syndrome. Issue 11 (7th September 2017) - Peters, T. M.; Pelletier, R.; Behlouli, H.; Rossi, A. M.; Pilote, L.
Abstract: Aim: Diabetes is a stronger risk factor for acute coronary syndrome for women than men. We investigate whether behavioural and psychosocial factors contribute to the disparity in acute coronary syndrome risk and outcomes among women with diabetes relative to women without diabetes and men. Methods: Among 939 participants in the GENESIS‐PRAXY cohort study of premature acute coronary syndrome (age ≤ 55 years), we compared the prevalence of traditional and non‐traditional factors by sex and Type 2 diabetes status. In a case‐only analysis, we used generalized logit models to investigate the influence of traditional and non‐traditional factors on the interaction of sex and diabetes. Results: In 287 women (14.3% with diabetes) and 652 men (10.4% with diabetes), women and men with diabetes showed a heavier burden of traditional cardiac risk factors compared with individuals without diabetes. Women with diabetes were more likely to be the primary earner and have more anxiety relative to women without diabetes, and reported worse perceived health compared with women without diabetes and men with diabetes. The interaction term for sex and diabetes (odds ratio (OR) 1.40, 95% confidence intervals (95% CI) 0.83–2.36) was diminished after additional adjustment for non‐traditional factors (OR 1.12, 95% CI 0.54–2.32), but not traditional factors alone (OR 1.41, 95% CI 0.84–2.36). Conclusions: We observed trends toward a more adverse psychosocial profile among women with diabetes and incident acute coronary syndrome compared with women without diabetes and men with diabetes, which may explain the increased risk of acute coronary syndrome in women with diabetes and may also contribute to worse outcomes. What's new?: Women with diabetes experience higher risk of mortality following acute coronary syndrome relative to women without diabetes as well as men overall. Because differences in the burden of traditional cardiovascular risk factors do not fully explain the excess incidence or decreased survival, we explored whether psychosocial factors may be more prevalent among women with diabetes. In our cohort, women with diabetes tended toward a more adverse psychosocial profile relative to women without diabetes and men with diabetes. We identify potentially modifiable factors that might alter cardiovascular risk and impact outcomes for women with diabetes following acute coronary syndrome.